Efficacy and safety of mirabegron for the treatment of low compliance bladder resulting from sacral/infrasacral lesions: A prospective study. (18th April 2020) - Vasudeva, Pawan; Yadav, Siddharth; Madersbacher, Helmut; Kumar, Niraj; Prasad, Vishnu; Saurav, Kumar; Kumar, Ramesh; Borah, Diganta
Abstract: Objective: To assess the efficacy and safety of mirabegron in patients with sacral/infrasacral lesions who have an acontractile detrusor and develop a low compliance bladder. Methods: This prospective study included adult patients with acontractile detrusor as a result of sacral/infrasacral lesions who develop a low compliance bladder (compliance <20 mL/cmH2 O). All patients were asked to make a 48‐h clean intermittent catheterization diary and underwent invasive urodynamics evaluation at the baseline, and were started on mirabegron 50 mg once daily. Patients were re‐evaluated at 6 weeks with a repeat clean intermittent catheterization diary and invasive urodynamics, and the efficacy and safety of mirabegron was assessed. Results: A total of 17 patients were included. After 6 weeks of mirabegron therapy, the number of patients reporting leakage in between clean intermittent catheterization reduced from seven to two ( P  = 0.02), the end filling pressures reduced from 41.4 to 15.1 cmH2 O ( P  = 0.003), the compliance increased from 9.8 to 99.9 mL/cmH2 O ( P  = 0.000), and the number of patients where the end filling pressure was >40 cmH2 O reduced from eight to one ( P  = 0.02). The cystometric bladder capacity did not change significantly. Similar effects were noted in patients who were already on clean intermittent catheterization or were started on clean intermittent catheterization at inclusion in the study. Mirabegron was well tolerated, none of the patients discontinued therapy or reported major side‐effects. Conclusions: Mirabegron reduces end filling pressure, improves compliance and is safe in patients with a low compliance bladder resulting from a sacral/infrasacral lesion.